REPRESENTASI MAKNA SIMBOLIK RUMAH ADAT SASADU - Kanda, Amrin (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi; Vol 15 No 2 (2019), 2020)
This study aims to describe the ritual procession in the Sasadu Traditional House and describe the meaning of the Sasadu traditional house which has become an icon of the Sahu ethnic community in South Halmahera Regency. The approach used in this research is qualitative research. Data collection techniques used include; observation, in-depth interviews and documentation. Data were analyzed based on communication ethnographic analysis. The results showed that the Sasadu traditional house is a typical house of the Sahu tribe in West Halmahera district which is used as a place to carry out the Horom toma Sasadu traditional ceremony (eat together in Sasadu). The implementation of the traditional ceremony is usually done at the time of the harvest as a form of gratitude and implementation of musyarawah